Odpowiedź:
Zad. 6
a) -2-3*5 = -2-15 = -17
b) (-8) :4 - 2 = -2 - 2 = -4
c) 12 : (-2) - (-3) = -6 + 3 = -3
d) (-2)³ * 3 - 25 = -8 * 3 - 25 = -24-25 = -49
e) (-15) : 3 - 5*(-1) = -5+5 = 0
f) 3 * (-7) - 7 * (-2)= -21 + 14 = -7
g) 6 * (-4) + 5 * (-9) = -24 - 45 = -69
h) (-18) :9 - (-27) :(-1) = -2 -27 = -29
i) [tex]\frac{24 - 36}{4} -7= \frac{-12}{4}-7=-3 - 7= -10[/tex]
j) [tex]\frac{-9-6}{-3}*(-4) = \frac{-15}{-3}*(-4) = 5 * (-4) = -20[/tex]
k) [tex]\frac{-9+5*(-11)}{4}=\frac{-9-55}{4}=\frac{-64}{4}=-16[/tex]
l) [tex]4 * \frac{-1-3}{-2-3}=4*\frac{-4}{-5}=\frac{16}{5}=3\frac{1}{5}[/tex]
Szczegółowe wyjaśnienie: